Antibacterial Activity of Siam Weed Extract (Chromolaena odorata L.) Against Streptococcus mutans and Pseudomonas aeruginosa Bacteria - I Putu Gede Adi Purwa Hita; Putu Padmidewi Wijaya Kusuma; Subhan Rullyansyah; Bagus Lanang Arinatha (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Infectious diseases are one of the main health problems in developed and developing countries. The prevalence of nosocomial infections reaches 15.74% and dental caries infections reach 88.8% caused by Pseudomonas aeruginosa and Streptocuccus mutans bacteria. To overcome bacterial infections, people usually use antibiotics, however, the use of antibiotics that are not appropriate and appropriate to the indications can cause antibiotic resistance or Antimicrobial Resistance (AMR). Therefore, this study aims to test the effectiveness of siam weed leaf extract (Chromolaena odorata L.) in inhibiting the growth of bacteria that cause infections. Siam weed leaf extract was prepared using the maceration method with 96% ethanolic solvent accompanied by extract quality control and active compound content testing. Antibacterial activity testing was carried out using the disc diffusion method to see and measure the area of inhibition zone. The results founded that siam extract has good water content, total ash content and weed acid insoluble ash content, which are below 10%, 16.6% and 0.7%. The antibacterial activity test of siam weed leaf extract obtained an inhibition zone diameter of 15.1 mm in Streptococcus mutans bacteria and 18.2 mm in Pseudomonas aeruginosa. In addition, siam weed extract also qualitatively contains active secondary metabolite compounds such as alkaloids, flavonoids, saponins, steroids, phenols and tannins. This concluded that siam weed leaves extract of has a characteristics that meet the requirements, containing secondary metabolite compounds and has antibacterial activity against the growth of Pseudomonas aeruginosa and Streptococcus mutans bacteria.